Probabilitas Praktik Predatory Pricing pada Kegiatan Usaha dengan Menggunakan Hasil Kejahatan sebagai Modal Usaha - Muh. Afdal Yanuar (Komisi Pengawas Persaingan Usaha, 2022)
Through this paper, the author will describe about the probability of Predatory Pricing practices using the proceeds of crime as a business capital in Indonesia, and the sanctions that should be imposed on such cases. This research is motivated by the potential for business actors to carry out predatory pricing because they have additional capital power that comes from criminal acts, which has happened in Pennsylvania in the 'Pizza Connection Case'. The type of research used in this paper is normative research with a conceptual, statute, and comparative approach. Through this paper, it can be concluded that: (a) In the scheme of using proceeds of crime in the business sector, the use of proceeds of crime as company capital can raise the probability of predatory pricing in the business sector, which causes competitors to go out of business, as in the case of the 'pizza connection cases' in Pennsylvania; and (b) In the event of a predatory pricing practice using the proceeds of a criminal act as business capital, business actors may be charged with money laundering, business competition crimes, and predicate crimes. As for the company itself, it is possible to be subject to money laundering by a corporation.